Formulation and Evaluation of Usiradi Yoga Ointment for Dermatological Conditions (International Journal of Ayurveda and Pharma Research, 2025)
The prevalence of skin and subcutaneous illnesses and the worldwide burden of skin disorders has increased significantly in recent times. In addition to physical health, these medical and cosmetic issues also affect mental health and self-esteem. In Ayurveda, skin conditions are mostly categorized under the spectrum of Kushta. Classical literature describes eighteen different forms of Kushtas, and their treatment. In the treatment of dermatological conditions, medicinal powders are utilized as external therapies in forms such as Lepa, Udwartana, and Udsadana. Nevertheless, using powder can cause discomfort and pain in certain skin conditions. Given today's fast-paced lifestyle, there is a need for a convenient dosage form made from easily available raw materials. The goal of this study is to formulate an ointment using Usiradi Yoga churna, mentioned in Vaidyamanorama (Chikilsa krama), and to improve patient compliance without compromising its efficacy. This report includes the development and quality analysis of Usiradi Yoga ointment (USYO). Fine powders of Vetiveria zizanoides, Soot, Plumbago zeylanica, Psoralea corylifolia, Pongamia pinnata, Piper longum triturated with cow’s urine distillate (3.16% each) were added to the liquid paraffin and bees wax mixture (6:1) as ointment base. In addition to physicochemical parameters, microbiological test and finger printing of phytochemical constituents of USYO was conducted. The Results showed that USYO was of good consistency and fair extrudability and successfully passed the microbiological test. HPTLC fingerprinting of USYO demonstrated the presence of several constituents.